Efektivitas Model Pembelajaran Contextual Teaching and Learning (CTL) Berbantuan Wordwall terhadap Peningkatan Hasil Belajar Siswa SMP pada Materi Jaringan Komputer - Abd. Aziz Bouty; Hermila A; Arip Mulyanto; Jemmy A. Pakaja; Muthia; Rhalia Adinda Lahay (Education and Information Technologies, 2025)
This study aims to determine the effectiveness of the Contextual Teaching and Learning (CTL) model assisted by Wordwall media on improving junior high school students' learning outcomes in computer networking material. The background of this study stems from students' low understanding of computer networking material and the dominance of conventional methods that make students passive in the learning process. The research used a quantitative approach with a One Group Pretest–Posttest Design. The research subjects were 24 eighth-grade students at SMP Negeri 2 Satap Tilongkabila. Data were collected through learning outcome tests administered before and after the implementation of the CTL model assisted by Wordwall. Data analysis was performed using the Shapiro-Wilk normality test and Paired Sample t-Test with the help of SPSS version 25. The results showed a significant increase in student learning outcomes, with a pretest average score of 43.58 and a posttest average score of 79.54. The t-test produced a significance value (Sig. 2-tailed) < 0.001 (< 0.05), which means that there was a significant difference between learning outcomes before and after the implementation of the learning model. Thus, the implementation of the CTL model assisted by Wordwall proved to be effective in improving student learning outcomes in computer network material